2020
DOI: 10.1016/j.neurobiolaging.2020.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Free-water metrics in medial temporal lobe white matter tract projections relate to longitudinal cognitive decline

Abstract: Although hippocampal volume has served as a long-standing predictor of cognitive decline, diffusion MRI studies of white matter have shown similar relationships. Still, it remains unclear if gray and white matter interact to predict cognitive impairment and longitudinal decline. Here, we investigate whether FW and FW-corrected fractional anisotropy (FA T ) within medial temporal lobe white matter tracts provides meaningful contribution to cognition and cognitive decline beyond hippocampal volume. Using data fr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(54 citation statements)
references
References 52 publications
8
46
0
Order By: Relevance
“…However, the magnitude of the mediation and the beta value of cortical thickness were the highest, suggesting that GM neurodegeneration has a stronger contribution to SCD as compared with the contribution of WM neurodegeneration. In prodromal AD, GM neurodegeneration seems to be downstream to WM neurodegeneration in longitudinal studies [60]. In cross-sectional studies, this nding may be re ected by a stronger association between GM neurodegeneration and cognition and a weaker association between WM neurodegeneration and cognition [61].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the magnitude of the mediation and the beta value of cortical thickness were the highest, suggesting that GM neurodegeneration has a stronger contribution to SCD as compared with the contribution of WM neurodegeneration. In prodromal AD, GM neurodegeneration seems to be downstream to WM neurodegeneration in longitudinal studies [60]. In cross-sectional studies, this nding may be re ected by a stronger association between GM neurodegeneration and cognition and a weaker association between WM neurodegeneration and cognition [61].…”
Section: Discussionmentioning
confidence: 99%
“…Because multiple pathologies usually coexist in the brain of cognitively unimpaired individuals [62,63], future studies should thus unveil the pathologies underlying non-AD patterns of GM and WM neurodegeneration in SCD. Investigating pathologies such as cerebrovascular disease and tauopathies is warranted due to their contribution to SCD in community-based cohorts [60,63,11,64]. A limitation of our cohort is that we do not have biomarkers for amyloid-beta and tau-related pathologies.…”
Section: Limitationsmentioning
confidence: 99%
“…Using this technique, reductions in white matter microstructure have been associated with higher levels of AD pathology in preclinical AD ( Hoy et al, 2017 ) and were more closely associated with AD pathology than conventional diffusion MRI metrics ( Walsh et al, 2020 ). Finally, our group recently demonstrated that FW-corrected measures interacted with hippocampal atrophy to predict more rapid rates of cognitive decline ( Archer et al, 2020 ). While FW-corrected metrics have been leveraged to evaluate several aspect of objective cognitive decline, they have not yet been used to assess SCD.…”
Section: Introductionmentioning
confidence: 99%
“…Archer et al [ 79 ] evaluated the baseline and longitudinal trajectory data on FW and free water-corrected FA (FA T ) within medial temporal WM tracts, including the cingulum bundle, fornix, tapetum, inferior longitudinal fasciculus, and uncinate fasciculus. At baseline, FA T in the tapetum and fornix and FW in all tracts were associated with hippocampal volume.…”
Section: Applications Of Advanced Diffusion Mri Techniques In Neurodegenerative Diseasesmentioning
confidence: 99%
“…Groups with and without hippocampal neurodegeneration groups (positive and negative groups, respectively) are based on the previously identified cut-off volume (positive: volume ≤6723 mm 3 [ 81 ]). Abbreviations: eMCI, early mild cognitive impairment; FA T , free water-corrected FA; FW, free water; ILF, inferior longitudinal fasciculus; MCI, mild cognitive impairment; UF, uncinate fasciculus (adapted and reproduced with permission from Archer et al [ 79 ]).…”
Section: Figurementioning
confidence: 99%